Strategi Komunikasi Pemasaran dalam Meningkatkan Penjualan Media Iklan Lift Poster PT. Ignite Technology Indonesia (Lifty Media) - Feby Sahri Frianto; Dani Setiadarma (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
This study aims to examine the marketing communication strategy and the implementation of Integrated Marketing Communication (IMC) in supporting the sales of elevator poster advertising media at PT Ignite Technology Indonesia (Lifty Media). A qualitative case study approach was employed using interviews, observation, and document analysis. The findings indicate that the strategy is formulated based on audience segmentation and building context, and implemented through structured personal selling activities. IMC is reflected in message consistency, internal coordination, and the integration of physical media with digital elements. Sales improvement is understood as a strategic contribution through offer relevance, communication consistency, and client relationship management in a B2B marketing context